Muḥāsabah as a Method for Improving Self-Regulated Learning Abilities - Aisyah, Hanna; Rohim, Muhammad (CV. Media Publikasi Profesional, 2021)
Every school certainly expects its students to be able to carry out the learning process optimally so that someday they become qualified people, both in terms of academics and personality. But in reality, efforts to foster students do not always run smoothly. There are many twists and turns of student problems that often arise, such as the lack of discipline, low learning motivation, and student attitudes and behavior that include low self-regulated learning. In overcoming these problems, muḥāsabah is the right method that every student needs to do. At SMA Plus Al-Ghifari, muḥāsabah has been used as a method as well as an activity in improving the personality quality of students. The purpose of this study is to find out more about the background of muḥāsabah activities at Al-Ghifari Plus High School, to know how the process of implementing muḥāsabah activities and to find out what are the roles of muḥāsabah in improving student self-regulated learning. This study uses a qualitative approach with descriptive methods and uses three data collection techniques in the form of observation, interviews, and copying documents. From this research, it is found that muḥāsabah has an important role in three aspects of life, namely spiritual aspects, social aspects, and educational aspects. As for the educational aspect, muḥāsabah plays an important role in improving students' self-regulated learning in the form of the growth of an attitude of responsibility, self-discipline, learning motivation, having targets and goals, good time management, and being able to solve problems in learning.